2007
DOI: 10.1309/crcu356u7146yc31
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Instability Is Uncommon in Lymphoepithelioma-like Carcinoma of the Lung

Abstract: Primary lymphoepithelioma-like carcinoma of the lung (LELC) shares some morphologic and clinical characteristics with malignancies associated with microsatellite instability (MSI). The aims of our study were to determine the MSI status in LELC and compare these findings with stage I non-small cell lung carcinoma (NSCLC) with marked lymphocytic host response (MLHR). We assessed MSI by a DNA-based polymerase chain reaction assay using mononucleotide (BAT25 and BAT26) and dinucleotide (D2S123, D5S346, and D17S250… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Furthermore, because of the lymphoepithelioma-like morphology, EBV infection was sought and found to be negative 36. This does appear to be a unique case and others have not found significant levels of MSI in lymphoepithelioma-like carcinomas of the lung, for instance 40. There are cases of colonic lymphoepithelioma-like carcinomas of the colon that are not arranged in syncytial sheets but rather as single cells, small clusters of tumour and occasional glands that have a predominant intra-tumoural lymphoid component.…”
Section: Lymphoepithelioma-like Carcinoma Of the Colonmentioning
confidence: 65%
“…Furthermore, because of the lymphoepithelioma-like morphology, EBV infection was sought and found to be negative 36. This does appear to be a unique case and others have not found significant levels of MSI in lymphoepithelioma-like carcinomas of the lung, for instance 40. There are cases of colonic lymphoepithelioma-like carcinomas of the colon that are not arranged in syncytial sheets but rather as single cells, small clusters of tumour and occasional glands that have a predominant intra-tumoural lymphoid component.…”
Section: Lymphoepithelioma-like Carcinoma Of the Colonmentioning
confidence: 65%
“…In the past two decades, there have been just over 150 cases reported in published work. (12,21,22) In our study, 16 patients were male and 30 patients were female. The male:female ratio was different from other published reports of 2.2:1 (23) and 6:5 (16) ; the male:female ratio of NSCLC was 2.2:1 in our previous study.…”
Section: Discussionmentioning
confidence: 82%
“…(24,27) The low frequency of association with cigarette smoking in LELC of the lung (13% in the current series and 40% in cases in published reports), (22,28) in contrast to other lung cancers (smoking history usually more than 60%), (29) suggests that smoking probably does not play an etiologic role, further mandating separation of this tumor from other lung cancers. (21,22) Considerable evidence indicates that the EGFR pathway also plays an important role in both the pathogenesis and the progression of lung cancer. (30) A detailed study of mutation patterns within the EGFR gene and their associations with clinicopathologic features of lung cancers suggested that lung cancer patients whose tumors have EGFR mutations respond better than those without such mutations to drugs that target the EGFR tyrosine kinase domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our cohort, we used the term "medullary" to refer to a poorly differentiated carcinoma with syncytial islands or complex collections of malignant cells exhibiting prominent infiltration by intraepithelial lymphocytes. It is noted that one can diagnose a "lymphoepithelioma-like" carcinoma when someone confronts an EBV+ medullary carcinoma, particularly in other parts of the body, 10,16,44 and we recognize that our definition of medullary carcinoma overlaps somewhat with "lymphoepithelioma-like" carcinoma in this sense. Using a similar definition, MSI-H status has been reported in 90% to 100% of medullary carcinomas of the colon, 1,21,32 which comprise only 4% of colorectal cancers.…”
Section: Am J Surg Patholmentioning
confidence: 83%